SISTEMADE INDICADORES DE CALIDAD I - García P., Manuel (2003)
The present essay deals with a Quality Indicators System likely to be adopted in organizations implementing their continuous quality and improvement systems. Relations among criterion, indicator and standard and their own examples, as well as the different kinds of indicators is shown.